The crystal structure of (E)-N ′-(2-bromobenzylidene)-2-naphthohydrazide, C36H26Br2N4O2 - Yuan Lin; Deng Shao-Wen; Liu Fang; Li Zhong-Yan (Zeitschrift für Kristallographie - New Crystal Structures)
C36H26Br2N4O2, triclinic, P1 (no. 1), a = 8.700(5) Å, b = 9.188(5) Å, c = 9.722(6) Å, α = 91.610(6)°, β = 91.436(6)°, γ = 100.925(6)°, V = 762.4(8) Å3, Z = 1, Rgt ${R}_{gt}$ (F) = 0.0381, wRref $wR_{ref}$ (F 2) = 0.1016, T = 296(2) K.